2018
DOI: 10.1093/scan/nsy057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of self-focus on personal and social foraging behaviour

Abstract: The continuous balancing of the risks and benefits of exploiting known options or exploring new opportunities is essential to human life. We forage for new opportunities when they are deemed to be more attractive than the available option, but this decision to forage also entails costs. People differ in their propensity to exploit or forage, and both the social circumstances and our individual value orientations are likely influences. Here, participants made foraging decisions for themselves and for a charity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
5
15
0
Order By: Relevance
“…Our results are silent on which of these variables better accounts for dACC activity during such a task, but our normative and empirical findings from Experiment 2 suggest a clear path towards resolving this question. Previous studies by Shenhav and colleagues applied this same approach to deconfound foraging value and choice conflict in a non-sequential foraging choice task (originating in [ 5 ]) and demonstrated that choice conflict consistently accounted for dACC activity during these choices better than foraging value [ 2 , 6 , 21 ]. While questions remain regarding whether foraging value signals might emerge by altering other properties of this experimental design (e.g., the reward-related cues), this approach was successful at unambiguously disentangling conflict and foraging value by enabling the authors to test for qualitatively distinct patterns of neural activity (i.e., ones that vary monotonically vs. non-monotonically).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are silent on which of these variables better accounts for dACC activity during such a task, but our normative and empirical findings from Experiment 2 suggest a clear path towards resolving this question. Previous studies by Shenhav and colleagues applied this same approach to deconfound foraging value and choice conflict in a non-sequential foraging choice task (originating in [ 5 ]) and demonstrated that choice conflict consistently accounted for dACC activity during these choices better than foraging value [ 2 , 6 , 21 ]. While questions remain regarding whether foraging value signals might emerge by altering other properties of this experimental design (e.g., the reward-related cues), this approach was successful at unambiguously disentangling conflict and foraging value by enabling the authors to test for qualitatively distinct patterns of neural activity (i.e., ones that vary monotonically vs. non-monotonically).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are silent on which of these variables better accounts for dACC activity during such a task, but our normative and empirical findings from Experiment 2 suggest a clear path towards resolving this question. Previous studies by Shenhav and colleagues applied this same approach to deconfounding foraging value and choice conflict in a non-sequential foraging choice task (originating in Kolling et al (2016)) and demonstrated that choice conflict consistently accounted for dACC activity during these choices better than foraging value (Shenhav, Straccia, et al, 2016;Shenhav et al, 2014;Zacharopoulos, Shenhav, Constantino, Maio, & Linden, 2018). It is therefore possible that a neuroimaging study of a deconfounded version of the pig dice task (e.g., our Experiment 2) would similarly demonstrate that activity previously attributed to switch value (e.g., cumulative sum of rewards) is better accounted for by choice conflict, but this awaits empirical testing.…”
Section: Discussionmentioning
confidence: 99%
“…In another study in humans, Zacharopoulos et al. (2018 ) required participants to make patch-leaving decisions, either to collect rewards for themselves or to collect rewards for a charity of their choice.…”
Section: Why Forage? Neural Mechanisms Revealed By Patch-leaving Paradigmsmentioning
confidence: 99%